PEMANFAATAN ENDEK SEBAGAI SEPATU GUNA MENARIK MINAT GENERASI MUDA MELESTARIKAN BUDAYA BALI - Dharmayoga, I Dewa Gede Ari; Putra, Gede Wirabuana; Priantono, I Made Endra (Program Kreativitas Mahasiswa - Kewirausahaan, 2013)
Entrepreneurship Student Creativity Program featuring a distinctive innovative use of fabrics bali (endek fabric) as an attractive shoe in the present. Endek shoe aims to create a generation of young love against the fabric so that the fabric endek remain stable and do not become extinct. Endek shoe has a promising business opportunity because this endek new shoes were first produced in Bali and have quite a lot of interest so that the shoe is endek very high chance to develop.